Integrating Adabul ‘Alim wal Muta’allim into EFL Teacher Professional Identity in the Indonesian Islamic University Context - Nuskhan Abid; Rudi Hartono; Rahayu Puji Haryanti; Hendi Pratama; Siti Marpuah; Eko Widianto (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
The integration of religious ethics within English as a Foreign Language (EFL) remains underdeveloped, often sidelined by an epistemological dichotomy between general and religious disciplines. This study investigates how the ethical dimensions of K.H. Hasyim Asy’ari’s classical text, Adabul ‘Alim wal Muta’allim, are integrated into the professional identity and pedagogical practices of English teachers at an Indonesian Islamic university. Employing a narrative inquiry, data were collected through in-depth interviews with five English teachers and observations. Findings indicate that the integration of adab is manifested in (1) intention and sincerity as part of teacher identity, (2) teachers as exemplary models of Islamic ethics, (3) Islamic ethics as non-discrimination and fairness pedagogy, and (4) harmonious relationships to foster an inclusive learning environment. Practical manifestations of adab integration in the teaching process include fair assessment practices and extraordinary patience with students' grammatical and pronunciation errors. This study contributes to Islamic education by providing a clear framework to bridge knowledge gaps and eliminate scientific dichotomies between secular language teaching and religious ethics, and offering an in-depth model for a holistic teacher identity. This study offers a model for updating the curriculum to integrate strong language skills with the development of religious ethics in teacher professional identity construction and pedagogical practices.